ANALISIS DAMPAK KERUSAKAN REKAM MEDIS PASIEN RAWAT JALAN TERHADAP KEJADIAN PATIENT SAFETY, RESPONSE TIME PELAYANAN PASIEN DAN PENGAJUAN KLAIM BERKAS PASIEN RAWAT JALAN PESERTA BPJS KESEHATAN DI RUMAH SAKIT ISLAM IBNU SINA SIMPANG EMPAT KABUPATEN PASAMAN BARAT - Aulia Fajri Safar; Bambang Hadi Kartiko; I Wayan Nurata (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
Based on initial observations in November 2022-January 2023, 375 damaged medical records were found at RSI. Ibn Sina Simpang Empat. The impact of tampering with medical records on the incidence of patient safety in target I was 124, target II was 36, and target III was 56. Impact on service response time that was not appropriate was 235 patients. The impact on  submitting BPJS claims was delayed by 157 patients. The research objective was to determine the impact of damage to outpatient medical records at RSI Ibnu Sina Simpang Empat.The research method is descriptive qualitative analysis. Respondents who were interviewed were 8 respondents with a supporting sample of 826 damaged outpatient medical records. Data collection techniques used are interviews and observation. The results showed that damaged medical records had an impact on the incidence of patient safety, target I resulted in an error in identifying the patient, target II broke the communication between the service provider and the patient and target III resulted in an error in administering medication to the patient. Impact on inappropriate service response time (> 10 minutes). The impact on the delayed submission of BPJS claims is that the workload increases. The impact of damage to medical records on patient safety, service response time, and submission of BPJS claims. have patient data backups, provide standard time for providing medical records, and provide roll o pack cabinets.